Macroeconomic theory - Vaish, M. C. (New Delhi Vikas, 1999)
Thoroughly revised and updated in every aspect by incorporating the latest available literature on macroeconomics. At several places new diagram have been added as well as latest theoretical literature.
Includes bibliographical references and indexes.
oif 09/02/16
Loans
Keywords: Macroeconomics; Macroeconomic theory